'Ground Hog Da Din' for the Sikh insurgency?. (17th February 2021) - Fair, C. Christine; Ashkenaze, Kerry; Batchelder, Scott
ABSTRACT: Between 1978 and 1992, Sikh militants rampaged across the northern Indian state of the Punjab demanding that a homeland for Sikhs, called Khalistan, be carved from that state. The so-called Khalistanis, with Pakistan's extensive support, waged a brutal campaign of violence that killed tens of thousands. While Indian security forces eviscerated the various Khalistani groups by 1992, support for the movement remained strong in pockets of the global Sikh diaspora. Pakistan's intelligence agency, the ISI, also worked to keep the movement alive wherever possible. Pakistan's efforts have paid off: in recent years, the Khalistan movement has rehabilitated itself even within India. We constructed a novel dataset of Khalistani terror incidents perpetrated in the last decade. These data demonstrate the revivification of Khalistani terrorism, with perduring support from the ISI, which has engineered connections among Khalistani activists, militants operating in Kashmir, and narcotics traffickers. We argue that the renaissance of Khalistan is part of Pakistan's strategy to wage proxy warfare under its nuclear umbrella as a substitution strategy for its use of Islamist proxies, such as Lashkar-e-Tayyaba and Jaish-e-Mohammad, which has become more constrained by international pressure.